Mensintesis Dampak Sosial Ekonomi Wakaf dan Zakat terhadap Pertumbuhan Berkelanjutan dalam Ekonomi Kreatif Halal - Masyhuri, Muallif; Annissa, Ella (EKOBIS SYARIAH, 2026)
Not many studies systematically explain the combined impact of waqf and zakat on sustainable growth in the context of the halal creative economy, especially from the socio-economic side such as poverty alleviation, equal opportunity distribution, empowerment of halal creative SMEs, and their long-term impact. This research aims to synthesise empirical evidence from the literature regarding the influence of waqf and zakat on the socio-economics of the halal creative economy, as well as to identify the factors that strengthen or hinder their role in achieving sustainable growth. The method used is a literature review or systematic mapping. About 30 journal articles were selected based on inclusion criteria: publications between 2020–2025, containing discussions on waqf, zakat, halal creative economy, or sustainable growth. The results show that productive waqf and productive zakat can enhance the capacity of the halal creative economy through the provision of capital, access to financing, training and mentoring, and regulatory support. Digitalisation and institutional integration also emerged as important factors. As a main finding, it produces an integrative zakat-waqf model that maps the flow of resources from collection (nazhir/amil), productive distribution, to strengthening the capacity of halal creative economy actors (SMEs). This article is expected to contribute to theory and practice by offering a framework on how waqf and zakat can be maximised as instruments for inclusive and sustainable halal creative economy growth, as well as policy recommendations to overcome major obstacles.